Digitalisasi Profil Usaha Siomay Batagor Bogarasa Melalui Perancangan Website Berbasis Odoo - Erika Fitriyani; Sri Bekti Handayani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The use of information technology through website development has become a crucial need for MSMEs, including traditional food businesses like Siomay Batagor Bogarasa. This study aims to develop a business profile website using the Odoo-based ERP website module to strengthen brand identity and facilitate information delivery to customers. The development process follows the Software Development Life Cycle (SDLC) stages, including planning, requirement analysis, design, implementation, and testing. The developed website consists of several pages such as Home, About Us, Menu, and Contact Us, presenting information about the business history, product catalog and pricing, sales locations, and contact channels. Testing results indicate that most features function well, with responsive display, smooth navigation, active contact form, and effective social media integration. One issue was found in the Google Maps display, which has not yet accurately shown the business location. Overall, the website provides practical benefits in terms of promotion, communication, and enhancing the professionalism of the business.